The Dialogical Theatre - Harris, M. author. aut Link
XII, 211 p.
Keywords: In this adventurous and wide-ranging book, Harris weaves an intriguing tale of Franciscan Missionary theatre in early colonial Mexico and Indigenous dramatizations of the theme of conquest in modern Mexico. He offers fresh readings of representations of the conquest of Mexico by Dryden and Artaud and engages in a lively dialogue with Bakhtin's insistence that drama is a monological genre. Combining careful scholarship and an entertaining style, he develops his study of the theatre into a thoughtful and original meditation on the ethics of cross-cultural encounter.